Adoption of e-learning in Zimbabwe’s higher education: Opportunities and challenges - Chikuvadze, Pinias; Zuva, Joseph; Mugijima, Samuel; Rusike, Patrick C. (Indonesian Journal of Learning Education and Counseling, 2025)
This paper explores the adoption of e-learning in Zimbabwe's higher education, examining the opportunities and challenges associated with its implementation in the teaching and learning process. The paper was grounded in a systematic review approach, which provides a holistic view of the issue under investigation. In this regard, the PRISMA 2020 checklist ensured transparency and consistency in selecting the 60 papers from databases (Scopus, DOAJ, DHTE, WoS, Scielo SA, and IBSS). In addition, this approach ensured that all the crucial aspects of the issue under investigation were included in the analysis and discussion. The paper highlights e-learning as a concept and its process in the context of higher education. It also articulated a multifaceted approach that can be employed to enhance the adoption of e-learning in higher education. This led to the interrogation of the potential of e-learning to enhance accessibility, reduce costs, and improve educational outcomes. However, it also identifies significant barriers, including limited internet connectivity, inadequate technological infrastructure and resistance to change from both lecturers and students. In conclusion the adoption of e-learning in Zimbabwe's higher education presents both significant opportunities and notable challenges. To unlock the full potential of e-learning, policymakers, educational institutions and stakeholders need to collaborate in addressing these challenges. Ultimately, with the right approach, e-learning can play a transformative role in improving the quality and accessibility of higher education in Zimbabwe, contributing to broader educational socio-economic development targets.